APPRAISAL OF MALAYSIAN AND NIGERIAN CRUDE KAOLIN RESOURCES FOR HEAT RESISTANCE APPLICATIONS - ABDULLAHI, TIJJANI; AMINU, NASIRU; ABUBAKAR, HAMZAT (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY (2536-6041), 2020)
At present, there has been a major increase in the development of green technologies and with the shortage of fossil energy around the globe, qualitative and quantitative improvement and effective application of natural resources are most keenly wished for, in terms of both the fundamental and industrial stands. In this study, we reported an effort towards internationalizing our endowed national resources through a comparative characterization of Malaysian (M-kaolin) and Nigerian (N-kaolin) crude kaolinite resources. The two kaolin resources hold similar crystallite structures with different thermal and pore size distribution properties, and the N-kaolin is containing a visible trace of Illite which presumably influenced the crystallinity of the crude kaolin. Thus, N-kaolin is highly promising for refractory applications.